IMPLEMENTATION OF SMART CITY TECHNOLOGIES IN HOUSING AND COMMUNAL SERVICES MANAGEMENT (Marketing Journal, 2025)
The article examines the theoretical and practical aspects of implementing “smart city” technologies in the management system of housing and communal services (HCS). The concept of a умный город is presented as an innovative model of urban infrastructure ba sed on digital platforms, the Internet of Things (IoT), artificial intelligence, and big data analytics. The study substantiates the need to shift from traditional management approaches in the HCS sector to intelligent, technology -driven methods that enhan ce efficiency, transparency, and sustainability.
Keywords: smart city; digitalization; housing and communal services; innovative management; Internet of Things; artificial intelligence; sustainable development; digital platforms. № 10-SON OKTA BR; 2025 -YIL 132